Doctors at times of national instability: What Balint seminars reveal. (January 2019) - Antoun, Jumana; Johnson, Alan; Clive, Brock; Romani, Maya
Background: It is not known in what ways is the doctor whose practice is secure in a clinic challenged to maintain a therapeutic doctor–patient relationship when confronting a flood of immigrants within a country that is politically volatile, internally fractionalized, and surrounded by sporadic military incursions? Methods: During Balint seminars, a family medicine resident presents a troubling case which all group members reflect upon from the perspective of the doctor, the patient, and their relationship. Balint leaders later debrief and review the work of the group. Lebanon has passed through many political, social, and religious conflicts and was affected by the onset of the Syrian Civil War in 2010. The Balint leaders had begun to see in resident case presentations reflections of war's disruption of the doctor–patient relationship. Two Balint leaders reviewed a log of all the cases between 2013 and 2016. Results: In our observations, the discussion of the presented cases mirrored the cultural, social, religious, and political context of the country. First, the political situation was reflected in the dynamics of the group: agitation, conflicts, hopelessness, and a search for norms. Second, the residents subconsciously chose words in their discussion that reflect the country's situation. Third, the presented case was stirred by a tragic war-related event. Conclusions: The social/political/religious context in which the physician is practicing distracts the doctor from fulfilling his/her professional role. Balint seminars are an example of direct, experiential learning that provide an excellent opportunity for the special training of primary care physicians who deal with refugees and citizens to self-reflect on war's impact on them and their profession.